Effect of sleep-disturbed breathing on maxillofacial growth and development in school-aged children. Issue 2 (3rd April 2021) - Murakami, Ayano; Kawanabe, Hitoshi; Hosoya, Hisashi; Fukui, Kazunori
ABSTRACT: Purpose : In children, snoring and apnoea cause impairments in growth, cognitive function, attention, and school performance. In this study, we aimed to identify the association between craniofacial disharmony and paediatric sleep-disordered breathing. Materials and Methods : Forty-one patients with malocclusion (19 boys; 22 girls; mean age, 10.0 ± 2.1 years) were selected from our hospital. The relationship between maxillofacial morphology, pharyngeal airway form, and nasal respiratory function was examined using cephalometric analysis and skeletal patterns. All patients underwent portable monitoring with an overnight out-of-centre sleep testing protocol that could be performed at home using a portable computerized monitoring system. Results : The respiratory disturbance index was significantly greater in patients with mandibular retrusion than those with malocclusion. Arterial oxygen saturation and nasopharyngeal area were significantly smaller in participants with Class II malocclusion than in those with other types of malocclusion. Moreover, dental cast model analyses confirmed that patients with reduced transverse maxillary dimensions had a higher obstructive sleep apnoea syndrome (OSAS) risk than those with malocclusion. Therefore, patients with mandibular retrusion have a higher OSAS risk than those with other types of malocclusion. Conclusion : Childhood maxillofacial morphology may influence adult OSAS, and early treatment for children with OSAS may help prevent adult OSAS.